KEKUATAN HUKUM KUASA MENJUAL DARI PERJANJIAN PENGIKATAN JUAL BELI YANG PEMBERI KUASANYA MENINGGAL DUNIA - Winahyu Erwiningsih (Lafadz Jaya Publisher, 2023)
The purpose of this study is to ascertain and evaluate the legal viability of the power of attorney to sell from the Sale and Purchase Binding Agreement used by the power of attorney to transfer ownership rights to land after the power of attorney's death. It also seeks to determine and evaluate the power of attorney to sell's validity period. Because this legal study employs normative-empirical techniques, it comprises of both field research—that is, research that is conducted directly on the ground to gather primary data—and literary research—that is, research that involves document studies to gather secondary data. The data that has been collected is qualitatively examined, i.e., issue solving is produced by merging the two data. This study reveals that even though the power of attorney to sell technically no longer exists due to the Sale and Purchase Binding Agreement (PPJB), its use is restricted by the land office's systems, such as the electronic checking system that verifies the identity of the authorizer during the registration process. To protect the interests of the buyer who had paid off all his obligations at the time of signing the PPJB, the power of sale does not specify the specific duration of validity and is only valid until the power of attorney is used. This allows the buyer to process the transfer of land rights at the Land Deed Making Office (PPAT) at any time after the ongoing processes have been finished